Longitudinal surveillance on antibiogram of important Gram-positive pathogens in Southern China, 2001 to 2015. (February 2017) - Xu, Zhenbo; Xie, Jinhong; Peters, Brian M.; Li, Bing; Li, Lin; Yu, Guangchao; Shirtliff, Mark E.
Abstract: Objectives: A longitudinal surveillance aimed to investigate the antibiogram of three genus of important Gram-positive pathogens in Southern China during 2001–2015. Methods: A total of 3849 Staphylococcus, Enterococcus and Streptococcus strains were isolated from Southern China during 2001–2015. Bacteria identification was performed by colony morphology, Gram staining, the API commercial kit and the Vitek 2 automated system. Antimicrobial susceptibility testing was determined by disk diffusion method and MIC method. Results: As sampling site was concerned, 51.4% of Staphylococcus strains were isolated from sputum, whereas urinary tract remained the dominant infection site among Enterococcus and Streptococcus . According to the antimicrobial susceptibility, three genus of important Gram-positive pathogens showed high resistance against erythromycin, tetracycline, ciprofloxacin and clindamycin. Resistance rates to penicillins (penicillin, oxacillin, ampicillin) were high as well, with the exception of E. faecalis and Streptococcus . Overall, resistance rates against methicillin (oxacillin) were 63.2% in S. aureus and 76.2% in coagulase-negative Staphylococcus (CNS), along with continuous increases during the study. VRSA and vancomycin-resistant coagulase-negative Staphylococcus only appeared in 2011–2015. Sight decline was obtained for the vancomycin resistance of E. faecalis, while vancomycin-resistant E. faecium only appeared in 2011–2015, with its intermediate rate decreasing. Significant decrease in penicillin-resistant Streptococcus pneumonia (PRSP) was observed during studied period. Glycopeptide antibiotic remained highly effective to Staphylococcus, Enterococcus and Streptococcus (resistance rates <5%). Conclusions: Despite decline obtained for some antibiotic agents resistance during 2001–2015, antimicrobial resistance among Gram-positive pathogens still remained high in Southern China. This study may aid in the guidance for appropriate therapeutic strategy of infections caused by nosocomial pathogens. Highlights: 3, 849 Gram-positive strains were collected during 2001–2015. 63.2% of S. aureus were MRSA; vancomycin-resistant Staphylococcus only appeared in 2011–2015. VRE ( E. faecium) only appeared in 2011–2015, with intermediate rates decreasing over the whole study period. Antimicrobial resistance still remains high; resistance declined on some antimicrobial.